(untitled) (Research, Society and Development, 2022)
This paper shows the use of dimension stone waste in the manufacture of soil-cement bricks. Initially, a sample of the soil was analyzed for mineralogical composition, particle size distribution (classifying it in the proportion of silt, sand, and clay), and physical performance by plasticity (Atterberg limits specified by standard NBR 7180). A series of soil/waste/cement mixtures were prepared with contents up to 90% wt.% of dimension stone waste. The samples were characterized as mineralogical composition, microstructure, and water absorption after 7, 14, 21, 28, and 60 days. The composition with 20% wt.% of dimension stone waste presented individual and average values of water absorption according to the conditions established by standard NBR ABNT 10834 (≤22% and ≤20% respectively) and the other samples presented similar results, indicating that the dimension stone waste could be used for production of soil-cement bricks, helping to reduce the environmental impacts of the dimension stone industry.